Screening and Identification of Heavy Metal Resistant Endophytic Fungi Isolated from Solanum nigrum and Heavy Metal Impact on Survivability of Earthworm - Prabha , N.; Vivekanandhan , S.; Aswinanand , B.; Sivanantham , S.; Sivakalai , S.; Begam , A. Khurshidh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Aim: Heavy metals are hazardous for both human health and the environment. In order to create and maintain contamination free soil, many efforts are made to develop economically feasible technologies. This research article emphasizes on phytoremediation by endophytic fungi (Alternaria alternata) isolated from leaves of Solanum nigrum. Materials and Methods: The endophytic fungus was confirmed by 18S rRNA sequencing. Isolated endophytic fungi was screened individually for heavy metal tolerance at various concentrations to Lead acetate (Pb), Magnesium chloride (Mg), Cadmium sulphate (Cd) and Potassium dichromate (Cr). Results: The endophytic fungi Alternaria alternate showed greater tolerance against the heavy metal cadmium. The minimum inhibitory activity of the fungi against the heavy metals showed maximum inhibition towards cadmium up to 6000ppm. The metal tolerance index showed maximum growth of Alternaria alternate towards cadmium, followed by other heavy metals Bioaccumulation of heavy metals by the endophytic fungi also demonstrated high tolerance against cadmium (89%). To determine the survivability of earthworm, toxigenicity test was done, the cadmium treated Earthworm was motionless within few minutes after exposure to cadmium when compared with control. Conclusion: Thus, the study clearly indicates that the endophytic fungi is a boon to control environmental pollution and to retain soil fertility.